Concepts, Conceptualization, and Conceptions in Geography. Issue 1 (2nd January 2019) - Lane, Rod; Carter, Jennifer; Bourke, Theresa
Abstract: This article explores concepts and the conceptualization process in geography. Much of the literature around these ideas uses terminology and ontological descriptions in multiple ways, leading to complexity and confusion when applied to pedagogical practice. Equally, the use of the term "concept" can depend on the context. We synthesize some of the overlapping categories by defining the nature of concepts in geography. Then we outline the process of conceptualization (development of deep understanding) and the role of alternative conceptions. Finally, we explain how students' alternative conceptions can be restructured to master threshold concepts, and outline the implications for geographical educators in terms of pedagogy.